2020
DOI: 10.1021/acsami.0c12930
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Generation of Reactive Species by Cold Plasma in Gelatin Solutions for Selective Cancer Cell Death

Abstract: Atmospheric pressure plasma jets generate reactive oxygen and nitrogen species (RONS) in liquids and biological media, which find application in the new area of plasma medicine. These plasma-treated liquids demonstrated recently to possess selective properties on killing cancer cells and attract attention towards new plasma-based cancer therapies. These allow for local delivery by injection in the tumor but can be quickly washed away by body fluids. By confining these RONS in a suitable biocompatible delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 75 publications
1
51
0
Order By: Relevance
“…The biological effects of plasma and plasma generated chemistry are dependent on the surrounding liquid environment [15][16][17][18]. In fact, studies have indicated immense variability in the biological effects attributed to cold plasma, depending on both the composition of the sample substrate and that of the ionized gas.…”
Section: Introductionmentioning
confidence: 99%
“…The biological effects of plasma and plasma generated chemistry are dependent on the surrounding liquid environment [15][16][17][18]. In fact, studies have indicated immense variability in the biological effects attributed to cold plasma, depending on both the composition of the sample substrate and that of the ionized gas.…”
Section: Introductionmentioning
confidence: 99%
“…Cold plasma has received considerable attention for its potential biomedical applications, including blood coagulation, wound healing, sterilization/inactivation, skin regeneration, oral health, and cancer therapy [4,32,33]. The efficiency of plasma for biomedical applications mainly relies on the ROS/RNS generated in it [34,35]. As shown in Figures 2d, 4b, and 5b, the tiny plasma jet is an ideal ROS/RNS source, and ROS/RNS intensity increases when the plasma jet is used nearer to tissues and conductive materials.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, CAP-treated foetal bovine serum (FBS), acting as a model for complex bio-fluids, shows not only cytotoxic effects but also exhibits increased mutagenic potential [18]. Compared to water, a higher production of reactive species (H 2 O 2 and NO 2 − ) can be detected in 2% gelatine polymer solution after CAP treatment, with RONS amounts generated in up to 12-times higher concentration, thus resulting in its higher efficiency to kill U-2 OS bone cancer cells [19]. Likewise, CAP treated DMEM shows increased effect on proliferation and apoptosis of A431 and HaCaT cutaneous squamous carcinoma cells, compared to CAP treated PBS, though intracellular ROS levels are more increased in the latter [20].…”
Section: Effects Of Plasma-activated Liquidsmentioning
confidence: 99%